Pendekatan Fraud Hexagon Model terhadap Indikasi Kecurangan Laporan Keuangan pada PT.Wijaya Karya (Persero) Tbk - Tsamarah, Niki; Elyanti Rosmanidar (Akubis : Jurnal Akuntansi dan Bisnis, 2025)
PT Wijaya Karya (Persero) Tbk, which consistently shows low in financial performance, has led to allegations of fraudulent financial statements behind this research. The main objective and focus of the research is to analyze indications of fraudulent financial statements at PT Wijaya Karya (Persero) Tbk using the fraud hexagon model. The type of data used in this research is secondary data in the form of annual reports from 2016-2023 which come from the official website of PT Wijaya Karya (Persero) Tbk. The analysis technique in this research is qualitative with a descriptive approach. Based on the research findings, the Fraud Hexagon Model consists of 6 elements, where Stimulus (ROA) can detect indications of fraudulent financial statements. Meanwhile, capability (change of directors), collusion (concurrent positions), opportunity (BDOUT), Rationalization (change of auditors), and Ego (frequency of CEO photos in the annual report) cannot detect fraudulent financial statements at PT Wijaya Karya (Persero) Tbk.